Manifestation of quantitative traits in the hybrids F1 of tomato parental forms which contained increased levels of lycopene in fruits - Рудас, Л. А. (Scientific Progress & Innovations, 2012)
Investigation the tomato hybrids F1 quantitative traits has shown that total yield, number of fruits per plant, number of commodity fruits per plant are manifested by the type of overdominance; weight of commodity fruit – overdominance, dominance and intermediate inheritance; interval between appearance of vigorous shoots and beginning of ripening number – dominance, intermediate inheritance and overdominance by example 47 of hybrid combinations, parental forms of which were varieties and lines of different groups ripening and parental forms – carriers of genes Bog, hp, dg: Manapal lines, Dark green (dg), Mоrioka 17, МО 112 (hp), PU-74-43 (Bog).